Microwave-Assisted Synthesis of Taxol Side-Chain Precursor from Malonic Acid - Ehsan, S.; Khan, B.; Ara, J. (Asian Journal of Chemistry, 2012)
Being a complex diterpenoid, the potent anticancer drug, taxol requires complicated multistep for its synthesis. Due to the chemical complexity of taxol, its commercial production by total synthesis is not likely to be economical. Another natural product, 10-deacetyl baccatin 111 is readily available in higher yield. Several methods have been reported for the synthesis of taxol by coupling baccatin 111 and the N-benzoyl-b-phenyl isoserine side chain. In this study, a simple precursor of side chain has been synthesized under microwave radiation by the condensation of benzaldehyde, ammonium acetate and malonic acid. The time required for the resulting b-amino acid was remarkably reduced from 6 h to 30 s only along with rapid, easy, simple and safe methodology. The structure elucidation of synthesized compound was done by its melting point, solubility, TLC techniques and spectral analyses.